’’Stop Bullying’’ ,Meningkatkan Kesadaran dan Empati Siswa Melalui Metode Brainstorming - Rustam Aji; Dewi Lusiana; Leni Marlina; Sherly Ratih Frichesyarius Santi Ajhie; Roro Ajhie Ayuningtya; Wirawan Shakty; Agus Setia Budi; Anas Kiki Anugrah (CV. CENDIKIA JENIUS INDONESIA, 2025)
This community service activity aimed to increase students’ awareness and empathy toward bullying behavior through the implementation of the brainstorming method in a school setting. The program was conducted at SMK 10 Rejang Lebong and involved 35 students from grades X, XI, and XII, as well as teachers and educational staff. The implementation method applied a Participatory Action Research (PAR) approach, including interactive health education sessions, case studies, group discussions, and simulation through role-playing. Evaluation was carried out using pre-test and post-test instruments to measure changes in students’ understanding. The results showed a significant improvement in students’ knowledge and awareness of bullying, including its definition, types, impacts, and prevention strategies. The percentage of correct responses increased from 5.71% in the pre-test to 94% in the post-test regarding bullying prevention, and from 8.57% to 91.4% regarding the effectiveness of the brainstorming method. In conclusion, the brainstorming method proved effective as an educational strategy to promote a safe, inclusive, and bullying-free school environment.